Early evaluation of anti-angiogenic effects with gadolinium(III) labeled APN/CD13 specific binding peptides magnetic resonance imaging - Sheng Han; Song-Song Liu; Gong-Wei Jing; Pin-Qin Wang; Yan-Teng Zhang; Ling Xiong; Ying-Fang Zhang; Hua-Sheng Qu; Bing-Xiu Ren (Scientific Reports)
Abstract Anti-angiogenesis has been recognized as a crucial strategy in anti-tumor therapy, and the early assessment of its efficacy is equally significant. In this study, we developed a magnetic resonance (MR) probe specifically targeting angiogenesis to facilitate targeted imaging for the early evaluation of anti-angiogenic effects. We synthesized DOTA-G3CNGRC, conjugated it with gadolinium(III), and subsequently evaluated the labeled probe in vitro. The tumor-bearing mouse models of HT-29 (negative for CD13 expression) and HT-1080 (positive for CD13 expression) were successfully established. Magnetic resonance imaging was conducted via intraperitoneal injection of labeled probes and Gd-DOTA, both before and after treatment with ubenimex at a dose of 0.5 mg/kg/day for seven consecutive days. The average signal intensity ratio of the transplanted tumor (target tissue, T) to the left hind leg (non-target tissue, NT) was determined using the region of interest technique (ROI), while changes in tumor size were meticulously recorded. Additionally, APN/CD13 expression levels in transplanted tumors were assessed both prior to and following treatment. The labeling rate of probes was 88.99%. The IC50 of the probes was 7.03 µM. The T/NT ratio of HT-1080 was significantly higher than that of HT-29 (P < 0.001, n = 5). Following treatment, the T/NT ratio of the HT-1080 transplanted tumors was significantly reduced (P < 0.001, n = 5), accompanied by a notable decrease in CD13 expression and negligible changes in the sum of the long and short diameters (P = 0.39, n = 5). The research findings revealed that Gd-DOTA-G3CNGRC can serve as a highly specific gadolinium-based magnetic resonance imaging probe for monitoring the efficacy of anti-angiogenic therapy.